Role of condensates in modulating DNA repair pathways and its implication for chemoresistance - Giuseppe Dall’Agnese; Alessandra Dall’Agnese; Salman F. Banani; Marta Codrich; Matilde Clarissa Malfatti; Giulia Antoniali; Gianluca Tell (2023)
For cells, it is important to repair DNA damage, such as double-strand and single-strand DNA breaks, because unrepaired DNA can compromise genetic integrity, potentially leading to cell death or cancer. Cells have multiple DNA damage repair pathways that have been the subject of detailed genetic, biochemical, and structural studies. Recently, the scientific community has started to gain evidence that the repair of DNA double-strand breaks may occur within biomolecular condensates and that condensates may also contribute to DNA damage through concentrating genotoxic agents used to treat various cancers. Here, we summarize key features of biomolecular condensates and note where they have been implicated in the repair of DNA double-strand breaks. We also describe evidence suggesting that condensates may be involved in the repair of other types of DNA damage, including single-strand DNA breaks, nucleotide modifications (e.g., mismatch and oxidized bases), and bulky lesions, among others. Finally, we discuss old and new mysteries that could now be addressed considering the properties of condensates, including chemoresistance mechanisms. For cells, it is important to repair DNA damage, such as double-strand and single-strand DNA breaks, because unrepaired DNA can compromise genetic integrity, potentially leading to cell death or cancer. Cells have multiple DNA damage repair pathways that have been the subject of detailed genetic, biochemical, and structural studies. Recently, the scientific community has started to gain evidence that the repair of DNA double-strand breaks may occur within biomolecular condensates and that condensates may also contribute to DNA damage through concentrating genotoxic agents used to treat various cancers. Here, we summarize key features of biomolecular condensates and note where they have been implicated in the repair of DNA double-strand breaks. We also describe evidence suggesting that condensates may be involved in the repair of other types of DNA damage, including single-strand DNA breaks, nucleotide modifications (e.g., mismatch and oxidized bases), and bulky lesions, among others. Finally, we discuss old and new mysteries that could now be addressed considering the properties of condensates, including chemoresistance mechanisms. Chemical changes in DNA can be highly harmful to living organisms. DNA, like other molecules, can undergo multiple chemical reactions. These reactions can occur spontaneously or as a result of exposure to chemicals or radiation (1Lindahl T. Instability and decay of the primary structure of DNA.Nature. 1993; 362: 709-715Crossref PubMed Scopus (4388) Google Scholar). When these reactions result in altered DNA structure, including base excision and DNA breaks, DNA damage can block gene expression and replication negatively affecting cell homeostasis, function, and survival (2Alhmoud J.F. Woolley J.F. Al Moustafa A.E. Malki M.I. DNA damage/repair management in cancers.Cancers (Basel). 2020; 121050Crossref PubMed Scopus (96) Google Scholar). Thus, DNA damage has to be promptly and properly repaired by the cells to allow for organism survival. Decades of investigation into DNA damage repair pathways have shed light on diverse cellular pathways responsible to resolve various types of DNA damage. These pathways include base excision repair (BER), nucleotide excision repair (NER), homologous recombination (HR), mismatch repair (MMR), and non-homologous end joining (NHEJ) (3Chatterjee N. Walker G.C. Mechanisms of DNA damage, repair, and mutagenesis.Environ. Mol. Mutagen. 2017; 58: 235-263Crossref PubMed Scopus (801) Google Scholar, 4Huang R. Zhou P.K. DNA damage repair: historical perspectives, mechanistic pathways and clinical translation for targeted cancer therapy.Signal. Transduct Target. Ther. 2021; 6: 254Crossref PubMed Scopus (121) Google Scholar). Dozens of different proteins must be efficiently recruited at DNA damage sites where these proteins work in coordination to allow for proper DNA damage repair. Structure-based studies and genetic studies have revealed interacting portions of proteins that allow for the recruitment of DNA damage repair proteins at sites of DNA lesions (5Perry J.J. Cotner-Gohara E. Ellenberger T. Tainer J.A. Structural dynamics in DNA damage signaling and repair.Curr. Opin. Struct. Biol. 2010; 20: 283-294Crossref PubMed Scopus (41) Google Scholar, 6Bigot N. Day M. Baldock R.A. Watts F.Z. Oliver A.W. Pearl L.H. Phosphorylation-mediated interactions with TOPBP1 couple 53BP1 and 9-1-1 to control the G1 DNA damage checkpoint.Elife. 2019; 8e44353Crossref Scopus (23) Google Scholar, 7Sun Y. McCorvie T.J. Yates L.A. Zhang X. Structural basis of homologous recombination.Cell. Mol. Life Sci. 2020; 77: 3-18Crossref PubMed Scopus (54) Google Scholar, 8Blackford A.N. Jackson S.P. ATM, ATR, and DNA-PK: the trinity at the heart of the DNA damage response.Mol. Cell. 2017; 66: 801-817Abstract Full Text Full Text PDF PubMed Google Scholar, 9McPherson K.S. Korzhnev D.M. Targeting protein-protein interactions in the DNA damage response pathways for cancer chemotherapy.RSC Chem. Biol. 2021; 2: 1167-1195Crossref PubMed Google Scholar, 10Cleary J.M. Aguirre A.J. Shapiro G.I. D'Andrea A.D. Biomarker-guided development of DNA repair inhibitors.Mol. Cell. 2020; 78: 1070-1085Abstract Full Text Full Text PDF PubMed Scopus (113) Google Scholar). Moreover, great emphasis has been recently put also into disordered regions of proteins in concentrating molecules with shared function into subcellular compartments not enclosed within membranes, called biomolecular condensates (11Spegg V. Altmeyer M. Biomolecular condensates at sites of DNA damage: more than just a phase.DNA Repair (Amst). 2021; 106103179Crossref PubMed Scopus (25) Google Scholar, 12Jiang S. Fagman J.B. Chen C. Alberti S. Liu B. Protein phase separation and its role in tumorigenesis.Elife. 2020; 9e60264Crossref Scopus (41) Google Scholar, 13Tong X. Tang R. Xu J. Wang W. Zhao Y. Yu X. et al.Liquid-liquid phase separation in tumor biology.Signal. Transduct. Target Ther. 2022; 7: 221Crossref PubMed Scopus (9) Google Scholar). In this review, we summarize key features of biomolecular condensates and DNA damage repair pathways with a focus on the involvement of biomolecular condensates in DNA damage repair. We also discuss open questions in the field of DNA damage repair that could now be addressed considering condensates and condensate properties. A new emerging field of study in cell biology consists of the identification and characterization of biomolecular condensates. Condensates are defined as sub-cellular compartments that are not physically enclosed within membranes and can concentrate diverse molecules (including proteins and nucleic acids) (14Sabari B.R. Dall'Agnese A. Young R.A. Biomolecular condensates in the nucleus.Trends Biochem. Sci. 2020; 45: 961-977Abstract Full Text Full Text PDF PubMed Scopus (148) Google Scholar, 15Conti B.A. Oppikofer M. Biomolecular condensates: new opportunities for drug discovery and RNA therapeutics.Trends Pharmacol. Sci. 2022; 43: 820-837Abstract Full Text Full Text PDF PubMed Google Scholar) to compartmentalize biochemical reactions (14Sabari B.R. Dall'Agnese A. Young R.A. Biomolecular condensates in the nucleus.Trends Biochem. Sci. 2020; 45: 961-977Abstract Full Text Full Text PDF PubMed Scopus (148) Google Scholar, 16Banani S.F. Lee H.O. Hyman A.A. Rosen M.K. Biomolecular condensates: organizers of cellular biochemistry.Nat. Rev. Mol. Cell Biol. 2017; 18: 285-298Crossref PubMed Scopus (2427) Google Scholar, 17Harrison A.F. Shorter J. RNA-binding proteins with prion-like domains in health and disease.Biochem. J. 2017; 474: 1417-1438Crossref PubMed Scopus (252) Google Scholar, 18Shin Y. Brangwynne C.P. Liquid phase condensation in cell physiology and disease.Science. 2017; 357eaaf4382Crossref PubMed Scopus (1651) Google Scholar). The first condensates to be observed were the Nucleolus (19Sirri V. Urcuqui-Inchima S. Roussel P. Hernandez-Verdun D. Histochem. Cell Biol. 2008; 129: 13-31Crossref PubMed Scopus (308) Google Scholar) and the Cajal bodies (20Morris G.E. The Cajal Body.Biochim. Biophys. Acta. 2008; 1783: 2108-2115Crossref PubMed Scopus (148) Google Scholar). Thanks to the advancement of microscopy technologies and a growing scientific interest in those compartments, many other condensates have been discovered, including transcriptional condensates (21Sabari B.R. Dall'Agnese A. Boija A. Klein I.A. Coffey E.L. Shrinivas K. et al.Coactivator condensation at super-enhancers links phase separation and gene control.Science. 2018; 361eaar3958Crossref PubMed Google Scholar, 22Shrinivas K. Sabari B.R. Coffey E.L. Klein I.A. Boija A. Zamudio A.V. et al.Enhancer features that drive formation of transcriptional condensates.Mol. Cell. 2019; 75: 549-561.e547Abstract Full Text Full Text PDF PubMed Scopus (193) Google Scholar), nuclear speckles (23Spector D.L. Lamond A.I. Nuclear speckles.Cold Spring Harb. Perspect. Biol. 2011; 3a000646Crossref PubMed Scopus (539) Google Scholar), splicing condensates (24Guo Y.E. Manteiga J.C. Henninger J.E. Sabari B.R. Dall'Agnese A. Hannett N.M. et al.Pol II phosphorylation regulates a switch between transcriptional and splicing condensates.Nature. 2019; 572: 543-548Crossref PubMed Scopus (317) Google Scholar), constitutive heterochromatin condensates (25Keenen M.M. Brown D. Brennan L.D. Renger R. Khoo H. Carlson C.R. et al.HP1 proteins compact DNA into mechanically and positionally stable phase separated domains.Elife. 2021; 10e64563Crossref PubMed Scopus (37) Google Scholar, 26Strom A.R. Emelyanov A.V. Mir M. Fyodorov D.V. Darzacq X. Karpen G.H. Phase separation drives heterochromatin domain formation.Nature. 2017; 547: 241-245Crossref PubMed Scopus (993) Google Scholar, 27Larson A.G. Elnatan D. Keenen M.M. Trnka M.J. Johnston J.B. Burlingame A.L. et al.Liquid droplet formation by HP1α suggests a role for phase separation in heterochromatin.Nature. 2017; 547: 236-240Crossref PubMed Scopus (926) Google Scholar), stress granules (28Brangwynne C.P. Eckmann C.R. Courson D.S. Rybarska A. Hoege C. Gharakhani J. et al.Germline P granules are liquid droplets that localize by controlled dissolution/condensation.Science. 2009; 324: 1729-1732Crossref PubMed Scopus (1614) Google Scholar), signaling condensates (29Gao X.K. Rao X.S. Cong X.X. Sheng Z.K. Sun Y.T. Xu S.B. et al.Phase separation of insulin receptor substrate 1 drives the formation of insulin/IGF-1 signalosomes.Cell Discov. 2022; 8: 60Crossref PubMed Scopus (5) Google Scholar, 30Su X. Ditlev J.A. Hui E. Xing W. Banjade S. Okrut J. et al.Phase separation of signaling molecules promotes T cell receptor signal transduction.Science. 2016; 352: 595-599Crossref PubMed Scopus (625) Google Scholar, 31Ditlev J.A. Vega A.R. Koster D.V. Su X. Tani T. Lakoduk A.M. et al.A composition-dependent molecular clutch between T cell signaling condensates and actin.Elife. 2019; 8e42695Crossref PubMed Scopus (56) Google Scholar, 32Zamudio A.V. Dall'Agnese A. Henninger J.E. Manteiga J.C. Afeyan L.K. Hannett N.M. et al.Mediator condensates localize signaling factors to key cell identity genes.Mol. Cell. 2019; 76: 753-766.e756Abstract Full Text Full Text PDF PubMed Scopus (112) Google Scholar, 33Jaqaman K. Ditlev J.A. Biomolecular condensates in membrane receptor signaling.Curr. Opin. Cell Biol. 2021; 69: 48-54Crossref PubMed Scopus (0) Google Scholar, 34Case L.B. Ditlev J.A. Rosen M.K. Regulation of transmembrane signaling by phase separation.Annu. Rev. Biophys. 2019; 48: 465-494Crossref PubMed Scopus (139) Google Scholar, 35Zeng M. Chen X. Guan D. Xu J. Wu H. Tong P. et al.Reconstituted postsynaptic density as a molecular platform for understanding synapse formation and plasticity.Cell. 2018; 174: 1172-1187Abstract Full Text Full Text PDF PubMed Scopus (211) Google Scholar, 36Lin C. Suen M. Jeffrey P. Wieteska L. Stainthorp A. Seiler C. et al.Receptor tyrosine kinases regulate signal transduction through a liquid–liquid phase separated state.bioRxiv. 2019; ([preprint])https://doi.org/10.1101/783720Crossref Scopus (0) Google Scholar, 37Huang W.Y.C. Alvarez S. Kondo Y. Lee Y.K. Chung J.K. Lam H.Y.M. et al.A molecular assembly phase transition and kinetic proofreading modulate Ras activation by SOS.Science. 2019; 363: 1098-1103Crossref PubMed Scopus (0) Google Scholar, 38Zeng M. Shang Y. Araki Y. Guo T. Huganir R.L. Zhang M. Phase transition in postsynaptic densities underlies formation of synaptic complexes and synaptic plasticity.Cell. 2016; 166: 1163-1175Abstract Full Text Full Text PDF PubMed Scopus (300) Google Scholar, 39Dall'Agnese A. Platt J. Zheng M. Friesen M. Dall'Agnese G. Blaise A. et al.The dynamic clustering of insulin receptor underlies its signaling and is disrupted in insulin resistance.Nat. Commun. 2022; 13: 7522Crossref PubMed Scopus (1) Google Scholar), nuclear pore condensates (40Hampoelz B. Schwarz A. Ronchi P. Bragulat-Teixidor H. Tischer C. Gaspar I. et al.Nuclear pores assemble from nucleoporin condensates during Oogenesis.Cell. 2019; 179: 671-686Abstract Full Text Full Text PDF PubMed Scopus (45) Google Scholar), miRNA processing condensates (41Lee S.C. Martienssen R.A. Phase separation in plant miRNA processing.Nat. Cell Biol. 2021; 23: 5-6Crossref PubMed Scopus (2) Google Scholar), and DNA damage response (DDR) condensates (11Spegg V. Altmeyer M. Biomolecular condensates at sites of DNA damage: more than just a phase.DNA Repair (Amst). 2021; 106103179Crossref PubMed Scopus (25) Google Scholar, 42Kilic S. Lezaja A. Gatti M. Bianco E. Michelena J. Imhof R. et al.Phase separation of 53BP1 determines liquid-like behavior of DNA repair compartments.EMBO J. 2019; 38e101379Crossref PubMed Scopus (205) Google Scholar, 43Vítor A.C. Sridhara S.C. Sabino J.C. Afonso A.I. Grosso A.R. Martin R.M. et al.Single-molecule imaging of transcription at damaged chromatin.Sci. Adv. 2019; 5eaau1249Crossref PubMed Scopus (32) Google Scholar, 44Capozzo I. Iannelli F. Francia S. d'Adda di Fagagna F. Express or repress? The transcriptional dilemma of damaged chromatin.FEBS J. 2017; 284: 2133-2147Crossref PubMed Scopus (22) Google Scholar) (Fig. 1). The physicochemical properties of condensates suggest that they may have diverse functions in cells (45Alberti S. Gladfelter A. Mittag T. Considerations and challenges in studying liquid-liquid phase separation and biomolecular condensates.Cell. 2019; 176: 419-434Abstract Full Text Full Text PDF PubMed Scopus (1065) Google Scholar). Condensates may allow for fast adaptive responses to changes in the environment. They can buffer concentrations of proteins; concentrate proteins to activate biochemical reactions; or sequester proteins to inactivate biochemical reactions. Thanks to their specific viscoelastic properties, condensates could generate mechanical forces. Condensates may also act as filters, for example, the nucleopore condensates, which permit or deny the entry of molecules into the nucleus (30Su X. Ditlev J.A. Hui E. Xing W. Banjade S. Okrut J. et al.Phase separation of signaling molecules promotes T cell receptor signal transduction.Science. 2016; 352: 595-599Crossref PubMed Scopus (625) Google Scholar, 45Alberti S. Gladfelter A. Mittag T. Considerations and challenges in studying liquid-liquid phase separation and biomolecular condensates.Cell. 2019; 176: 419-434Abstract Full Text Full Text PDF PubMed Scopus (1065) Google Scholar, 46Li C.H. Coffey E.L. Dall'Agnese A. Hannett N.M. Tang X. Henninger J.E. et al.MeCP2 links heterochromatin condensates and neurodevelopmental disease.Nature. 2020; 586: 440-444Crossref PubMed Scopus (77) Google Scholar, 47Schmidt H.B. Görlich D. Transport selectivity of nuclear pores, phase separation, and membraneless organelles.Trends Biochem. Sci. 2016; 41: 46-61Abstract Full Text Full Text PDF PubMed Scopus (267) Google Scholar). Among the different physical models that could explain how condensates are formed, one of them is Liquid-Liquid Phase Separation (LLPS) (48Hyman A.A. Weber C.A. Jülicher F. Liquid-liquid phase separation in biology.Annu. Rev. Cell Dev. Biol. 2014; 30: 39-58Crossref PubMed Google Scholar). LLPS can be described as a thermodynamically driven phenomenon consisting of de-mixing of a solution into two or more distinct liquid phases. In the 1940s, Flory and Huggins described the ability of polymers, such as proteins, to self-organize into discrete liquid-like droplets (49Flory P.J. Thermodynamics of high polymer solutions.J. Chem. Phys. 1941; 9: 423-432Crossref Scopus (1278) Google Scholar, 50Huggins M.L. Solutions of long chain compounds.J. Chem. Phys. 1941; 9: 440Crossref Google Scholar), and over the last 10 years, many different proteins essential for life have been shown to be able to form dense phases resembling liquid-like droplets (14Sabari B.R. Dall'Agnese A. Young R.A. Biomolecular condensates in the nucleus.Trends Biochem. Sci. 2020; 45: 961-977Abstract Full Text Full Text PDF PubMed Scopus (148) Google Scholar, 16Banani S.F. Lee H.O. Hyman A.A. Rosen M.K. Biomolecular condensates: organizers of cellular biochemistry.Nat. Rev. Mol. Cell Biol. 2017; 18: 285-298Crossref PubMed Scopus (2427) Google Scholar, 21Sabari B.R. Dall'Agnese A. Boija A. Klein I.A. Coffey E.L. Shrinivas K. et al.Coactivator condensation at super-enhancers links phase separation and gene control.Science. 2018; 361eaar3958Crossref PubMed Google Scholar, 22Shrinivas K. Sabari B.R. Coffey E.L. Klein I.A. Boija A. Zamudio A.V. et al.Enhancer features that drive formation of transcriptional condensates.Mol. Cell. 2019; 75: 549-561.e547Abstract Full Text Full Text PDF PubMed Scopus (193) Google Scholar, 24Guo Y.E. Manteiga J.C. Henninger J.E. Sabari B.R. Dall'Agnese A. Hannett N.M. et al.Pol II phosphorylation regulates a switch between transcriptional and splicing condensates.Nature. 2019; 572: 543-548Crossref PubMed Scopus (317) Google Scholar, 51Henninger J.E. Oksuz O. Shrinivas K. Sagi I. LeRoy G. Zheng M.M. et al.RNA-mediated feedback control of transcriptional condensates.Cell. 2021; 184: 207-225.e224Abstract Full Text Full Text PDF PubMed Scopus (175) Google Scholar, 52Chatterjee S. Maltseva D. Kan Y. Hosseini E. Gonella G. Bonn M. et al.Lipid-driven condensation and interfacial ordering of FUS.Sci. Adv. 2022; 8eabm7528Crossref Scopus (0) Google Scholar) dividing the cellular milieu into a "condensed phase" and a "dilute phase" (45Alberti S. Gladfelter A. Mittag T. Considerations and challenges in studying liquid-liquid phase separation and biomolecular condensates.Cell. 2019; 176: 419-434Abstract Full Text Full Text PDF PubMed Scopus (1065) Google Scholar) (Fig. 2). Considering the potential impact of condensates in the biomedical field, it is important to determine what leads to the generation of those compartments. Over the years, different studies suggested that the formation of condensates is promoted by several factors, such as protein features (51Henninger J.E. Oksuz O. Shrinivas K. Sagi I. LeRoy G. Zheng M.M. et al.RNA-mediated feedback control of transcriptional condensates.Cell. 2021; 184: 207-225.e224Abstract Full Text Full Text PDF PubMed Scopus (175) Google Scholar, 53Dignon G.L. Best R.B. Mittal J. Biomolecular phase separation: from molecular driving forces to macroscopic properties.Annu. Rev. Phys. Chem. 2020; 71: 53-75Crossref PubMed Scopus (177) Google Scholar). Different protein domains are known to promote condensate formation, including structured domains and intrinsically disordered regions (IDRs)/low complexity domains (LCDs) (21Sabari B.R. Dall'Agnese A. Boija A. Klein I.A. Coffey E.L. Shrinivas K. et al.Coactivator condensation at super-enhancers links phase separation and gene control.Science. 2018; 361eaar3958Crossref PubMed Google Scholar, 53Dignon G.L. Best R.B. Mittal J. Biomolecular phase separation: from molecular driving forces to macroscopic properties.Annu. Rev. Phys. Chem. 2020; 71: 53-75Crossref PubMed Scopus (177) Google Scholar). Among the different domains that can play a role in condensate behaviors, IDRs have been studied also in health and disease contexts (54Darling A.L. Liu Y. Oldfield C.J. Uversky V.N. Intrinsically disordered proteome of human membrane-less organelles.Proteomics. 2018; 18e1700193Crossref PubMed Scopus (119) Google Scholar). There are different types of IDRs, including elastin-like polypeptides (55Muiznieks L.D. Sharpe S. Pomès R. Keeley F.W. Role of liquid-liquid phase separation in assembly of elastin and other extracellular matrix proteins.J. Mol. Biol. 2018; 430: 4741-4753Crossref PubMed Scopus (57) Google Scholar) and prion-like domains (56Kim H.J. Kim N.C. Wang Y.D. Scarborough E.A. Moore J. Diaz Z. et al.Mutations in prion-like domains in hnRNPA2B1 and hnRNPA1 cause multisystem proteinopathy and ALS.Nature. 2013; 495: 467-473Crossref PubMed Scopus (1023) Google Scholar), and can be enriched in charged amino acids (57Miyagi T. Yamazaki R. Ueda K. Narumi S. Hayamizu Y. Uji I.H. et al.The patterning and proportion of charged residues in the arginine-rich mixed-charge domain determine the membrane-less organelle targeted by the protein.Int. J. Mol. Sci. 2022; 23: 7658Crossref PubMed Scopus (1) Google Scholar, 58Uversky V.N. Gillespie J.R. Fink A.L. Why are "natively unfolded" proteins unstructured under physiologic conditions?.Proteins. 2000; 41: 415-427Crossref PubMed Google Scholar). Several studies tried to investigate the relevance of IDR composition to condensate formation. IDRs seem to preferentially form condensates with specific partners that show similar physicochemical characteristics and behavior, including charge–charge interactions and hydrophobic interactions (59Lyons H. Veettil R.T. Pradhan P. Fornero C. De La Cruz N. Ito K. et al.Functional partitioning of transcriptional regulators by patterned charge blocks.Cell. 2023; 186: 327-345.e328Abstract Full Text Full Text PDF PubMed Scopus (0) Google Scholar). Considering the importance of protein–protein interactions for condensate formation, it is reasonable to think that it would be possible to artificially design molecules that will alter condensate formation for therapeutic purposes. Kameda and colleagues artificially designed small peptides that either promoted or impaired the formation of p53 condensates in vitro. This approach could also be taken to design peptide-therapeutics to alter condensate properties in cells (60Kamagata K. Ariefai M. Takahashi H. Hando A. Subekti D.R.G. Ikeda K. et al.Rational peptide design for regulating liquid-liquid phase separation on the basis of residue-residue contact energy.Sci. Rep. 2022; 1213718Crossref Scopus (5) Google Scholar). IDRs are not the only drivers of condensate formation. Indeed, nucleic acids have been shown to play important roles in promoting the formation of several condensates, including nuclear speckles (61Ilık İ A. Aktaş T. Nuclear speckles: dynamic hubs of gene expression regulation.FEBS J. 2021; 289: 7234-7245Crossref PubMed Scopus (28) Google Scholar), stress granules (62Wheeler J.R. Matheny T. Jain S. Abrisch R. Parker R. Distinct stages in stress granule assembly and disassembly.Elife. 2016; 5e18413Crossref Scopus (409) Google Scholar), and transcriptional condensates (21Sabari B.R. Dall'Agnese A. Boija A. Klein I.A. Coffey E.L. Shrinivas K. et al.Coactivator condensation at super-enhancers links phase separation and gene control.Science. 2018; 361eaar3958Crossref PubMed Google Scholar). Notably, there is evidence of RNA involvement in controlling the formation and dissolution of condensates (63Sharp P.A. Chakraborty A.K. Henninger J.E. Young R.A. RNA in formation and regulation of transcriptional condensates.RNA. 2022; 28: 52-57Crossref PubMed Scopus (13) Google Scholar). RNA can interact with the charged residues of IDRs. One example is the RNA-mediated feedback model proposed by Young and colleagues (51Henninger J.E. Oksuz O. Shrinivas K. Sagi I. LeRoy G. Zheng M.M. et al.RNA-mediated feedback control of transcriptional condensates.Cell. 2021; 184: 207-225.e224Abstract Full Text Full Text PDF PubMed Scopus (175) Google Scholar) in which transcribed RNAs, such as short enhancer-RNA, initially stimulate the formation of transcriptional condensates by increasing the weak multivalent interactions between RNA and components of the transcriptional condensates. RNA appears to favor condensate formation until the overall charge of the condensate is zero (charge-balance model). At this point, further transcription of RNAs, including both enhancer-RNA and pre-mRNA, leads to the dissolution of the condensate. Moreover, also different structural protein subdomains can promote condensate formation, such as the SH3 domain (64Amaya J. Ryan V.H. Fawzi N.L. The SH3 domain of Fyn kinase interacts with and induces liquid-liquid phase separation of the low-complexity domain of hnRNPA2.J. Biol. Chem. 2018; 293: 19522-19531Abstract Full Text Full Text PDF PubMed Scopus (27) Google Scholar) and the α-helical structure (65Conicella A.E. Dignon G.L. Zerze G.H. Schmidt H.B. D'Ordine A.M. Kim Y.C. et al.TDP-43 α-helical structure tunes liquid-liquid phase separation and function.Proc. Natl. Acad. Sci. U. S. A. 2020; 117: 5883-5894Crossref PubMed Scopus (152) Google Scholar). Genomic DNA is constantly subjected to endogenous and environmental threats, such as oxidative stress, alkylation, UV-damage, chemotherapeutics, and so on. These threats can damage the DNA, and unrepaired or incorrectly repaired DNA lesions could result in mutations or chromosomal rearrangements and aberrations. These alterations could lead to genomic instability, which is the basis of several human pathologies, ranging from cancer to neurodegenerative diseases (66Postel-Vinay S. Vanhecke E. Olaussen K.A. Lord C.J. Ashworth A. Soria J.C. The potential of exploiting DNA-repair defects for optimizing lung cancer treatment.Nat. Rev. Clin. Oncol. 2012; 9: 144-155Crossref PubMed Scopus (89) Google Scholar, 67Hanahan D. Weinberg R.A. Hallmarks of cancer: the next generation.Cell. 2011; 144: 646-674Abstract Full Text Full Text PDF PubMed Scopus (44586) Google Scholar). Different DNA repair pathways are responsible for the specific recognition and repair (or tolerance) of specific DNA lesions. These pathways work together, as an orchestra, in playing the symphony of DDR in a cell-type-, cell-cycle stage- and chromatin context-dependent manner (68Vaddavalli P.L. Schumacher B. The p53 network: cellular and systemic DNA damage responses in cancer and aging.Trends Genet. 2022; 38: 598-612Abstract Full Text Full Text PDF PubMed Scopus (0) Google Scholar, 69Jackson S.P. Bartek J. The DNA-damage response in human biology and disease.Nature. 2009; 461: 1071-1078Crossref PubMed Scopus (3969) Google Scholar, 70Polo S.E. Jackson S.P. Dynamics of DNA damage response proteins at DNA breaks: a focus on protein modifications.Genes Dev. 2011; 25: 409-433Crossref PubMed Scopus (844) Google Scholar, 71van Attikum H. Gasser S.M. Crosstalk between histone modifications during the DNA damage response.Trends Cell Biol. 2009; 19: 207-217Abstract Full Text Full Text PDF PubMed Scopus (416) Google Scholar, 72Yasuhara T. Zou L. Impacts of chromatin dynamics and compartmentalization on DNA repair.DNA Repair (Amst). 2021; 105103162Crossref PubMed Scopus (4) Google Scholar). There are three main classes of DNA repair pathways. The first class consists of DNA repair pathways that act at a single base level on non-distorting DNA lesions, such as the BER pathway. The BER pathway repairs the majority of oxidative and alkylating damages to the DNA through specific removal of the damaged base. It also repairs single-strand breaks (SSBs) through PARP recognition (73Caldecott K.W. DNA single-strand break repair and human genetic disease.Trends Cell Biol. 2022; 32: 733-745Abstract Full Text Full Text PDF PubMed Scopus (0) Google Scholar, 74Saville K.M. Clark J. Wilk A. Rogers G.D. Andrews J.F. Koczor C.A. et al.NAD(+)-mediated regulation of mammalian base excision repair.DNA Repair (Amst). 2020; 93102930Crossref PubMed Scopus (13) Google Scholar, 75Caldecott K.W. Mammalian DNA base excision repair: dancing in the moonlight.DNA Repair (Amst). 2020; 93102921Crossref PubMed Scopus (37) Google Scholar). The second class includes the NER pathway, which is involved in repairing distorting lesions such as those deriving from bulky adducts and UV-induced DNA damage. The NER pathway repairs DNA lesions by first excising and degrading a short stretch of ssDNA containing the damaged base and then by restoring the correct nucleotides in a polymerization-dependent manner (76Apelt K. Lans H. Schärer O.D. Luijsterburg M.S. Nucleotide excision repair leaves a mark on chromatin: DNA damage detection in nucleosomes.Cell. Mol. Life Sci. 2021; 78: 7925-7942Crossref PubMed Scopus (12) Google Scholar, 77Duan M. Speer R.M. Ulibarri J. Liu K.J. Mao P. Transcription-coupled nucleotide excision repair: new insights revealed by genomic approaches.DNA Repair (Amst). 2021; 103103126Crossref PubMed Scopus (11) Google Scholar, 78Krasikova Y. Rechkunova N. Lavrik O. Nucleotide excision repair: from molecular defects to Neurological Abnormalities.Int. J. Mol. Sci. 2021; 22: 6220Crossref PubMed Scopus (12) Google Scholar). The third class of DNA repair pathways is the MMR, whose role is to correct DNA polymerase misincorporation errors ensuring the highest level of fidelity of the DNA replication process. MMR repairs several errors through excision and polymerization-dependent replacement of the DNA strand containing the mismatch (Fig. 3). These errors usually originate following: (i) mismatches occurring during DNA replication; (ii) a minority of single oxidative lesions to G, or (iii) the formation of bulges at highly repeated short oligonucleotide sequences, which are involved in trinucleotide expansion defects (79Elez M. Mismatch repair: from preserving genome